Targeted Funding for Anti-Trafficking Initiatives: An evidence-based anti-oppressive approach - Nichols, Andrea; Preble, Kathleen (Anti-Trafficking Review, 2024)
Community-driven research is key to creating evidence-based collaborative systems that meet the multifaceted needs of human trafficking survivors and address oppressions that create vulnerabilities to human trafficking. Programmes and solutions require money and evidenced-informed processes, or they risk investing in systems that will not meet the needs of the intended target populations. This paper reflects on how a community-initiated research project influenced funding to enhance anti-trafficking work in a Midwestern US state. We urge other regions to adopt this model of research and resource allocation in their own anti-trafficking efforts.